PROMOTION OF COMMUNITY OCCUPATIONAL HEALTH AND SAFETY IN THE COFFEE PLANTATION SECTOR POS UKK MALANGSARI - Mury Ririanty; Reny Indrayani; Iken Nafikadini (UPT Penerbitan Universitas Jember, 2022)
Based on the Kalibaru Kulon Health Center dataset, which was reported in January-September 2021, there were 193 plantation workers who visited the Puskesmas and experienced an illness. The results of the observations show that members of the UKK Malangsari Post who are coffee plantation workers are not fully disciplined in the use of Personal Protective Equipment (PPE) while working so they are vulnerable to hazards in the workplace which in turn can cause health problems and even work accidents. This is caused by a lack of understanding of the function of PPE. The problem-solving framework in this activity is realized by increasing knowledge and understanding of the function of using PPE in the workplace. Implementation activities are carried out by promoting health with hybrid counseling techniques (offline and online) and making health promotion media in the form of leaflets and videos by involving local coffee plantation workers. The conclusion of this activity as a whole this community service activity can be said to be successful because of an increase in the knowledge of the target audience about the importance of using PPE at work and an increase in the positive attitude of the target audience towards the importance of using PPE in the workplace. . It is recommended that similar activities be carried out using attractive health promotion media not only by local UKK POS officers but also by companies that employ coffee workers in the Malangsari area. Keywords: Health Promotion, UKK Post, PPE, Plantation, Coffee